(untitled) (SCIÉNDO INGENIUM, 2022)
The objective of this research was to determine the procedures and methods of the billing system, as well as to optimize the management of non-tax revenues, in order to guarantee the economic sustainability of the Specialized Hospital III - Víctor Lazarte Echegaray in the city of Trujillo. The research that was presented was applied with a non-experimental, cross-sectional descriptive design. The personalized technique was the documentary analysis; the population was constituted by the documentation of the 10 Assistance Centers of the La Libertad Assistance Network. The sample was the Level III Specialized Hospital - Víctor Lazarte Echegaray in the city of Trujillo. The results show that the fulfillment of the quarterly goals scheduled during the first of 2020 is not as expected, in the second quarter the goal is achieved, but it is still low according to the evaluation criteria of the Institutional Operating Budget. It was concluded that the Financial Management in the Specialized Hospital III Víctor Lazarte Echegaray of the La Libertad Assistance Network is deficient, because the proposed goals, guidelines and compliance with the provisions issued by the superior areas are not met.